Differential Dynamic and Structural Behavior of Lipid-Cholesterol Domains in Model Membranes - Aguilar, Luis F.; Pino, José A.; Soto-Arriaza, Marco A.; Cuevas, Francisco J.; Sánchez, Susana; Sotomayor, Carlos P. (PLOS ONE, 2012)
Changes in the cholesterol (Chol) content of biological membranes are known to alter the physicochemical properties of the lipid lamella and consequently the function of membrane-associated enzymes. To characterize these changes, we used steady-state and time resolved fluorescence spectroscopy and two photon-excitation microscopy techniques. The membrane systems were chosen according to the techniques that were used: large unilamellar vesicles (LUVs) for cuvette and giant unilamellar vesicles (GUVs) for microscopy measurements; they were prepared from dipalmitoyl phosphatidylcholine (DPPC) and dioctadecyl phosphatidylcholine (DOPC) in mixtures that are well known to form lipid domains. Two fluorescent probes, which insert into different regions of the bilayer, were selected: 1,6-diphenyl-1,3,5-hexatriene (DPH) was located at the deep hydrophobic core of the acyl chain regions and 2-dimethylamino-6-lauroylnaphthalene (Laurdan) at the hydrophilic-hydrophobic membrane interface. Our spectroscopy results show that (i) the changes induced by cholesterol in the deep hydrophobic phospholipid acyl chain domain are different from the ones observed in the superficial region of the hydrophilic-hydrophobic interface, and these changes depend on the state of the lamella and (ii) the incorporation of cholesterol into the lamella induces an increase in the orientation dynamics in the deep region of the phospholipid acyl chains with a corresponding decrease in the orientation at the region close to the polar lipid headgroups. The microscopy data from DOPC/DPPC/Chol GUVs using Laurdan generalized polarization (Laurdan GP) suggest that a high cholesterol content in the bilayer weakens the stability of the water hydrogen bond network and hence the stability of the liquid-ordered phase (Lo).